Management of operation and maintenance practices in photovoltaic plants: Key performance indicators - Rediske, Graciele; Michels, Leandro; Cezar Mairesse Siluk, Julio; Donaduzzi Rigo, Paula; Brum Rosa, Carmen; Jochann Franceschi Bortolini, Ricardo (International journal of energy research, 2022)
Summary The number of large photovoltaic (PV) power plants is increasing around the world. Energy sale usually follows demand contracts with clearly defined obligations, subject to nonsupply penalties. Not supplying the amount of contracted energy is a critical issue to PV plant performance, which can be mitigated with operation and maintenance (O&M) good practices. Furthermore, as the PV plant ages, O&M practices become increasingly important to improve or maintain a good performance. Performance assessment is a complex process that involves several parameters to collect, indicators to measure, and action plans to solve the identified problems. The objective of this study is to identify relevant factors in performance evaluation of O&M practices of medium to large PV plants. Through a systematic literature review and Delphi method with specialists, 33 key performance indicators (KPIs) were determined and classified in operation or maintenance categories, and further in technical or economic subcategories. This paper also organized a set of parameters that PV plant managers should collect to determine the KPIs and evaluate the O&M practices performance. Efficient management of O&M practices results in an indirect increase in generation capacity, as well as ensuring compliance with electricity supply contracts. Photovoltaic plant monitoring